La lex Caecilia Didia: una importante disposizione in un momento di crisi - Sanguinetti, Andrea (Tesserae iuris, 2023)
The lex Caecilia Didia was proposed in 98 BC. by the two consuls Q. C. Metellus Nepos and T. Didius. The author goes back to the origin of the law, identifying in the strained political situation that characterizes the beginning of the first century BC., and in the attempt of the nobilitas to react to the unscrupulous policy of some tribunes of the plebs, characterized by an often aggressive and disrespectful use of the customs hitherto practiced in popular legislation, the main reasons for its proposition. The aim pursued by the law was to guarantee a correct development of the legislative process, starting from the promulgatio up to the moment of the vote. The individual provisions of the law all aimed to ensure that the people were adequately informed about the content of the rogatio and that they had the possibility to choose, in the event of several heterogeneous provisions, which to approve and which to reject. To the extent that it is believed that the law also contained a ban on having laws passed by vim, it would also have aimed at ensuring that popular legislative assemblies were protected from intimidation and violence. It seems less likely that the law contained a specific provision concerning the respect of auspicia, given that that matter had already been regulated by the leges Aelia et Fufia. The lex Caecilia Didia was finally equipped with a sanctioning apparatus which gave the senate the power to invalidate the law or at least remove its effects.